International Federation of Perioperative Nurses IFPN - A new organization for perioperative nurses: New partnerships for ORNAC - Hay, Vija (Operating Room Nurses Association of Canada Journal, 1999)
ORNAC has been participating in the development and formation and is a member of the International Federation of Perioperative Nurses (IFPN).